Architect's legal handbook the law for architects - Speaight, Anthony; Thorne, Matthew (New York, NY Routledge, 2021)
Architect's Legal Handbook is the most widely used reference on the law for practicing architects and the established textbook on law for architectural students. Since the last edition of this book in 2010 the legal landscape in which architecture is practised has changed significantly: the long-standing procurement model with an architect as contract administrator has been challenged by the growing popularity of design and build contracts, contract notices in place of certificates, and novation of architect's duties. The tenth edition features all the latest developments in the law which affect an architect's work, as well as providing comprehensive coverage of relevant UK law topics. Key highlights of this edition include: an overview of the legal environment, including contract, tort and land law. analysis of the statutory framework, including planning law, health and safety, construction legislation and building regulations in the post-Grenfell legal landscape. procurement, and the major industry construction contract forms. building dispute resolution, including litigation, arbitration, adjudication and mediation. key fields for the architect in practice, including architects' registration and professional conduct, contracts with clients and collateral warranties, liability in negligence and insurance. entirely new chapters on various standard form contracts, architects' responsibility for the work of others, disciplinary proceedings, and data protection. tables of cases, legislation, statutes and statutory instruments give a full overview of references cited in the text. The Architect's Legal Handbook is the essential legal reference work for all architects and students of architecture".
Introduction to English law / Anthony Speaight QC -- The English law of contract / Anthony Speaight QC -- The English law of tort / Vincent Moran -- English land law / Martin Dixon -- Introduction to Scots law / Catherine Devaney -- Scots land law / Catherine Devaney -- Statutory authorities in England and Wales / James Strachan -- Statutory authorities in Scotland / Robin Fletcher -- Construction legislation in England and Wales / Martin Edwards and Murray Armes -- Building Regulations in Scotland / David Wedderburn -- Planning law in England and Wales / Andrew Fraser-Urquhart -- Planning law in Scotland / Michael Upton -- Public procurement under European Union law / Stephen Mavroghenis -- Party walls / Graham North -- Health and safety law affecting architects / Richard Dyton -- Introduction to procurement methods in construction / John Salway -- The JCT Standard Form of Building Contract, 2005 edition / Allen Dyer -- The NEC Engineering and Construction Contract and related architects' forms / Gordon Hall -- Other standard forms of building contract / Gordon Hall -- Contractor and sub-contractor collateral warranties/third party rights / Ann Minogue -- The FIDIC contract / Jeremy Glover -- The Construction Act Payment Rules / Matthew Needham-Laing -- Litigation / Anthony Speaight QC -- Arbitration / Melanie Willems -- Adjudication / David Friedman QC -- Mediation / Christopher Miers -- Building dispute resolution in Scotland / Robert Howie -- International arbitration / Tony Dymond and Emelita Robbins -- Legal organisation of architects' offices / Graham Brown -- Architects' contracts with clients / Sarah Lupton -- Architects' collateral warranties / Ann Minogue -- Architects' liability / James Cross QC -- Architects' professional indemnity insurance / James Leabeater -- Copyright / Clive Thorne -- Architects and the law of employment / Ruth Downing -- International work by architects / Richard Dyton -- Architects' registration / Sarah Lupton -- Professional conduct of architects / Sarah Lupton and Peter Anderson.
Includes bibliographical references and index.
Keywords: Architects -- Legal status, laws, etc. -- Great Britain; Architectural contracts -- Great Britain; Building laws -- Great Britain